2015
DOI: 10.3906/sag-1407-120
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its association with obesity among schoolchildren aged 6–15 living in Sakarya Province in Turkey

Abstract: IntroductionObesity and obesity-related disorders are worldwide concerns in both developing and developed countries. Since many kinds of chronic metabolic diseases are associated with obesity, the management of obesity and other related disorders has been the focus of investigation. Hypertension is a major chronic disorder, which is associated with obesity (1). The prevalence of childhood hypertension has been increasing; it currently occurs at a rate of 1%-2% in developed countries and a rate of 5%-10% in dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
3
9
0
1
Order By: Relevance
“…In this study, we also found that children with overweight/obesity have higher prevalence of hypertension, which was in consistent with other research results [21,22]. e odds ratio of developing hypertension in overweight and obese children were 1.5 and 3.6 times more than those with a normal weight and is consistent with the results of other studies [23].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we also found that children with overweight/obesity have higher prevalence of hypertension, which was in consistent with other research results [21,22]. e odds ratio of developing hypertension in overweight and obese children were 1.5 and 3.6 times more than those with a normal weight and is consistent with the results of other studies [23].…”
Section: Discussionsupporting
confidence: 93%
“…Our study, conducted in Turkish children aged 12 to 13 years, revealed more than one in 10 adolescents (12.7%) had EBP and nearly one in five (17.5%) had HT. This is in accordance with the higher prevalence of HT reported in some other European and Turkish studies [14,15,37]. In a survey conducted in Bursa, Turkey, including 1000 subjects aged 6-13 years, the proportion of children and adolescents with EBP and HT was reported to be 10.8% [14].…”
Section: Discussionsupporting
confidence: 88%
“…In a survey conducted in Bursa, Turkey, including 1000 subjects aged 6-13 years, the proportion of children and adolescents with EBP and HT was reported to be 10.8% [14]. In another study performed in Sakarya including 2166 children and adolescents aged 6-15 years, overall combined EBP and HT rates were determined to be 30.4%, while HT prevalence was found to be twice as high in children with obesity versus those without obesity [15]. Similarly, when BMI-based groups of overweight and obesity were taken, we determined an increased OR for obesity with systolic blood pressure (systolic EBP 2.4-fold, systolic HT 4.0-fold higher), diastolic blood pressure (diastolic EBP 2.5-fold, diastolic HT 3.0-fold higher), and overall systemic blood pressure (EBP 3.5-fold, HT 3.9-fold higher).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Middle-East region the limited data available regarding parental risk factors of childhood HTN is controversial. While some studies indicate the role of family history of HTN and obesity [16][17][18][19], others found no signi cant contribution of these factors in the development of high BP in children [20,21]. In Iran the family history of HTN and obesity has been suggested to be an independent risk factor for children's HTN [17].…”
Section: Introductionmentioning
confidence: 99%